PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP HARGA SAHAM PADA SUBSEKTOR BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2018-2022 - Aprianti, Vika; Eka Putra, Okta; Fadillah Sagita, Dena (Universitas Logistik dan Bisnis Internasional, 2024)
This research was conducted with the aim of knowing the description and influence of Return on Assets, Earning Pershare, Price Earning Ratio, Exchange Rates and Inflation on the share prices of the coal subsector listed on the Indonesia Stock Exchange (BEI) for 2018-2022. The research method used in this research is quantitative analysis with descriptive and verification methods to determine the description of internal factors (Return on Assets, Earning Pershare, Price Earning Ratio). This research uses secondary data in the form of annual reports from each company, with a sample size of 23 companies and 115 financial reports using non-probability sampling techniques, purposive sampling. Data testing techniques are carried out using classical assumption tests, multiple linear regression coefficient tests, coefficient of determination tests, and hypothesis tests. Based on the results of research using the determination test, it was found that the Return on Assets variable had an effect on stock prices by 3.7%, the Earning Pershare variable had an effect on stock prices by 8.6%, while the Price Earning Ratio variable had an effect on stock prices by 0.6%, The exchange rate variable has an effect on stock prices by 2.2% and the inflation variable has an effect on stock prices by 1%. The verification results found that the variable Return on Assets had an effect on stock prices, Earning Pershare had an effect on stock prices, Price Earning Ratio had no effect on stock prices, Exchange Rates had no effect on stock prices, Inflation had no effect on stock prices and the Variables Return on Assets, Earnings Pershare, Price Earning Ratio, Exchange Rate and Inflation were simultaneously found to have a significant influence on share prices.